EVALUATION OF HEALTH AND LIFESTYLE OF UNDERGRADUATE STUDENTS IN MUMBAI. - DNYANESH LIMAYE; ANVAY UKIDVE; SNEHA RATHI; JUHI CHAUDHARI; ADWAIT PRADHAN; RAHUL LALGE; MITTAL DARJI; VAIDEHI LIMAYE; GERHARD FORTWENGEL (International Journal of Pharma and Bio Sciences, 2015)
The overall development of a student is completely dependent on the ability of the student to cope up with the growing pressure of college and modern life mentally as well as socially. It is seen that this new setting brings about certain changes in the lives of students which either may have a positive or negative impact on their overall well-being. Many students get involved in unhealthy and risky lifestyle behaviours like alcohol abuse, tobacco use, physical inactivity and unhealthy dietary practices which may adversely affect their health in the long-term. In India, research with regard to health and lifestyle patterns amongst students remains limited. A cross sectional study was conducted to evaluate the health and lifestyle of students in Mumbai, India. Materials and methods: A total of 217 undergraduate students werescored using a validated Student health and lifestyle questionnaire’ to understand demographic details, lifestyle and health problems, and quality of life. Results and conclusion: 79.72 % students were assessed to be healthy, 94.47% abstained from consumption of alcohol, and 98.62% refrained from consumption of Tobacco. Data regarding quality of life (depression, anxiety and stress parameters) showed that the majority of students belonged to the normal category. The results of this study showed that the undergraduate students from Mumbai, India do not engage in unhealthy lifestyles and risky behaviours and have normal quality of life.